O Autoritarismo e a Incoerência dos Fenômenos Jurídicos no Contexto Judicial Brasileiro: o garantismo penal e o ativismo judicial - Costa, Oswaldo Poll (Universidade do Vale do Rio dos Sinos, 2018)
The present study approaches, initially, the intimate connection between legal phenomena with wide repercussion in Brazil - judicial activism and penal garantism - and the global context of crisis of the modern State. Nevertheless, starting from a historical analysis, we seek to demonstrate these phenomena follow a tradition of theories imported by national authors, that here acquired a new meaning, collaborating - unlike what they predict in thesis - more for the maintenance of our society’s structures than for its transformation. Thus, they contribut to the maintenance of an authoritarian and unequal society. We concluded, therefore, that the judicial activism practiced in Brazil is a contradiction. Concomitantly, it seeks inspiration in judicial practice and in the academic production of other countries and it is essentially Brazilian, because it has taken on its own meaning, connected to the intrinsic characteristics of our country. Some of these characteristics are approached in order to demonstrate their close connection with our authoritarian tradition. Following the same reasoning, we try to demonstrate when the constitutional guarantees are not uniformly assured to all, they lose their essential character, functioning like privileges, of which only enjoy those individuals that can afford a consistent defense in a eventual criminal action. Thereby, the social stigma left by the jail ends up falling on those individuals belonging to the poorest strata of the population, radically reducing any chance of their social ascension, as well as of the social group that surrounds them, collaborating for the maintenance of inequality. These factors, together, hamper the effective realization of fundamental / human rights in our society.
Keywords: Autoritarismo; Garantismo Penal; Ativismo judicial; Crise do Estado; Authoritarianism; Penal garantism; Judicial activism; Crisis of the state; ACCNPQ::Ciências Sociais Aplicadas::Direito